Analysis of the fire-extinguishing effect and the weakening of flame intensification of nonionic liquid water mist*. Issue 5 (3rd May 2020) - Jia, Hailin; Shen, Hedi; Xiang, Haijun; Li, Dihui; Zhai, Rupeng
ABSTRACT: The determination of a water mist additive is important to weaken the flame enhanced by water mist, which affects the safety and applicability of the water mist fire-fighting technology to a certain extent. Based on the theory of physical chemistry, in this study, a water mist additive, that is, a nonionic liquid alkyl phenol epoxide (APE) condensate to weaken the flame intensification and systematically perform an experimental study on extinguishing the fire in oil pool with nonionic liquid water mist. The results show that the nonionic liquid water mist has better atomization parameters. The extinguishing time and the maximum temperature are all decreased with the increase of nonionic liquid mass fraction under the action of nonionic liquid water mist. The maximum CO volume fraction and the time to maintain a high CO volume fraction in fire flue gas decreases with the increasing nonionic liquid mass fraction. The minimum O2 volume fraction and the recovery rate from this minimum value to the normal value increases with increasing nonionic liquid mass fraction. The nonionic liquid water mist can weaken the flame intensification and extinguish the oil pool fire better than pure water mist. This is because the suspended air and water bubbles formed after the spraying of the nonionic liquid water mist can block heat radiation, cutting off the oxygen supply and isolating the contact of combustibles with oxygen. In addition, owing to high temperature, surfactant and water molecules linked by hydrogen bond ether group rupture, resulting in reduced HLB, thus enhancing the ability to trap hydrocarbon molecules and capture H and OH radicals in the chain reaction.